Coping Strategies That Football Players Use During Ramadan Fasting: Turkish Super League Sample - Afacan, Ersin (Progress in Nutrition, 2021)
Study Objectives: This study aimed to investigate the self-created coping strategies of Muslim Turkish football players actively playing football in the Turkish Super League about fasting during the month of Ramadan. Because there were very few studies examining the subjective experiences of professional football players about fasting in Ramadan by using a qualitative method. Methods: 10 professional Muslim Turkish football players voluntarily participated in the study. The football players responded to an open-ended question about the coping strategies they applied during Ramadan. The responses given were interpreted in order to organize the subjective experiences of the football players about fasting. In the research, phenomenology design, which is one of the qualitative research methods, was used and inductive content analysis was performed. Results: The coping strategies of the football players were categorized in four dimensions as training, nutrition, lifestyle, and mental changes. These four general dimensions were classified into various sub-themes within themselves. It was also determined that the most frequently used strategies of the football players were the changes in training and nutrition. Conclusion: The coping strategies used by football players are not dependent on a specific scientific or philosophical model since they are based on subjective experiences. It is recommended that professional football players who fast during Ramadan should work with a mental trainer to be able to develop more effective coping strategies appropriate for their specific individual needs.